Factors affecting work life balance among workers in Ministry of International Trade and Industry (MITI) / Nur Atikah Kamis and Nurul Fatihah Anuar - Kamis, Nur Atikah; Anuar, Nurul Fatihah (Faculty of Business and Management, 2016)
This paper is to examine the factors affecting work life balance among MITI staff which is workload, role commitment and interpersonal relationship at work. Work life balance has become a top priority among employee and employees in organization. Nowadays, employees have facing the challenge of maintaining a balance between work life and personal life. Imbalance in work life will create a problem to employees in terms of life and workplace satisfaction. Work life balance is very important issues for those interested in quality of working life. In order to find out the factors affecting work life balance, the researchers had distributed 140 questionnaires to the MITI’s management staff. Descriptive analysis, reliability analysis, Pearson’s correlation analysis and multiple regression analysis were used in this study to identify the relationships between workload, role commitment and interpersonal relationship at work towards work life balance. Based on the findings, it shows that workload has negative and significant relationship with work life balance while role commitment and interpersonal relationship at work has positive and significant relationship with work life balance. It shows that role commitment is the most important factor that affecting work life balances among workers in MITI.